Management of post-cesarean uterine artery pseudoaneurysm in Indonesia - Charley Dokma Tua Simanjuntak, MD; Dedy Pratama, MD; Yuliardy Limengka, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Uterine artery pseudoaneurysm (UAP) is a rare but potentially serious complication of gynecologic and obstetric procedures, typically arising from traumatic injuries to the uterine artery wall. Diagnosis often involves Doppler sonography and arteriography, with transcatheter uterine artery embolization (UAE) emerging as an effective treatment option. We aim to present a case of UAP with a review of its diagnosis and management. We present a case of a 28-year-old female with prolonged vaginal bleeding following cesarean section, diagnosed with UAP via computed tomography angiography and successfully treated with embolization. Prompt diagnosis and intervention are crucial in managing UAP to prevent life-threatening complications.